PENGARUH PEMAPARAN Entamoeba gingivalis TERHADAP JUMLAH POLIMORFONUKLEAR NEUTROFIL (PMN) PADA TIKUS WISTAR JANTAN DENGAN RADANG GINGIVA - Dyaningsih, Dewi Maya; Praharani, Depi (Fakultas Kedokteran Gigi Universitas Jember, 2012)
Entamoeba gingivalis is one type of parasite that found in the gingival inflammation. Polymorphonuclearneutrophil (PMN) play a role at the beginning of inflammation. This study aims to determine the effect of exposure E.gingivalis to the number of PMN in Wistar male rats with gingival inflammation. The cervical of mandibular incisor ofall experimental animals was ligated with a wire to get the state of gingival inflammation and then they divided intotwo groups, namely control and treatment group. The control group was exposed to the physiological solution,whereas the treatment group were exposed to E. gingivalis for six days. Exposure performed one day after ligated.Data obtained by counting the number of PMN each group on days 4 and 7. The results show that the number ofPMN on the day of the 4th and 7th there was no significant difference between control and treatment group. Theconclusion of this study is the exposure of E. gingivalis did not affect the number of PMN in Wistar male rats withgingival inflammation.